KEPEMIMPINAN UNGGUL KEPALA SEKOLAH DASAR DAERAH TERPENCIL (Studi Multisitus pada Sekolah Dasar di Kabupaten Bondowoso) - Juharyanto (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2017)
Abstract: This study aims at describing the problem and capacity of leadership, the role of excellent leadership, and its behaviors of Elementary School’s Principal in remote areas. This research used the qualitative approach with multi-sites study design. The data were collected through in-depth interviews, participant observation, documentation and it analyzed inductively using modified analytic. The results showed that; 1) Elementary schools in remote areas have similar relative leadership problems and capacity; 2) there is four dominant excellent leadership played by the principal in realizing an effective school, among others: spiritual leadership, transformational leadership, the leadership of learning, and leadership of enterprener. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan problem dan daya dukung kepemimpinan, peran kepemimpinan unggul, dan perilaku kepemimpinan unggul Kepala SD daerah terpencil. Penelitian ini menggunakan pendekata kualitatif dengan rancangan studi multisitus. Data dikumpulkan melalui wawancara mendalam; observasi berperan serta; studi dokumentasi dan dianalisis secara induktif analitik yang dimodifikasi. Hasil penelitian menunjukkan; 1) SD di daerah terpencil memiliki problem dan dukungan kepemimpinan yang relatif sama; 2) terdapat empat kepemimpinan unggul dominan yang diperankan kepala sekolah dalam mewujudkan sekolah efektif, antara lain: kepemimpinan spiritual, kepemimpinan transformasional, kepemimpinan pembelajaran, dan kepemimpinan enterprener.